2021
DOI: 10.3389/fonc.2021.733763
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-Derived Fragment tRF-Glu-TTC-027 Regulates the Progression of Gastric Carcinoma via MAPK Signaling Pathway

Abstract: Transfer RNA-derived RNA fragments (tRFs) belong to non-coding RNAs (ncRNAs) discovered in most carcinomas. Although some articles have demonstrated the characteristics of tRFs in gastric carcinoma (GC), the underlying mechanisms still need to be elucidated. Meanwhile, it was reported that the MAPK pathway was momentous in GC progression. Thus we focused on investigating whether tRF-Glu-TTC-027 could act as a key role in the progression of GC with the regulation of the MAPK pathway. We collected the data of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…All studies examined pre‐selected candidate tRFs using real‐time quantitative PCR, and the number of tRFs examined in each study ranged from one to five. Seven studies 11 , 29 , 33 , 34 , 35 , 36 , 37 used a genome‐wide discovery approach with high throughput sequencing or small RNA sequencing to identify candidate tRFs, which were then validated in an independent cohort using qRT‐PCR. Using this approach, three of these three studies 11 , 32 , 33 selected a panel of tRFs to distinguish GC from normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…All studies examined pre‐selected candidate tRFs using real‐time quantitative PCR, and the number of tRFs examined in each study ranged from one to five. Seven studies 11 , 29 , 33 , 34 , 35 , 36 , 37 used a genome‐wide discovery approach with high throughput sequencing or small RNA sequencing to identify candidate tRFs, which were then validated in an independent cohort using qRT‐PCR. Using this approach, three of these three studies 11 , 32 , 33 selected a panel of tRFs to distinguish GC from normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…Through different regulatory mechanisms, tsRNAs can influence the process of tumorigenesis and progression (Anderson and Ivanov 2014 ; Schimmel 2018 ; Zhu et al 2019a , b ; Yu et al 2020 ). For example, Xu et al established that tRF-Glu-TTC-027 could inhibit the progress of GC by inhibiting the MAPK signaling pathway (Xu et al 2021 ). By targeting FBXO47, Zhang et al found that tRF-3019a promoted GC cell proliferation, migration, and invasion (Zhang et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that tsRNAs are closely associated with metastasis, proliferation, cell cycle, apoptosis, and drug-resistance. 22 , 23 For example, Hu et al reported that tsRNA-5001a promotes the proliferation of lung adenocarcinoma cells and increases the risk of postoperative recurrences in lung adenocarcinoma patients. 24 Zhou et al showed that tRF5-Glu contribute to the complex tumor heterogeneity of ovarian cancer cells and may provide new targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%